Question and Answers Forum

All Questions      Topic List

None Questions

Previous in All Question      Next in All Question      

Previous in None      Next in None      

Question Number 106488 by Algoritm last updated on 05/Aug/20

Commented by Dwaipayan Shikari last updated on 05/Aug/20

 Q106379  ((1.2^2 )/(10))+((2.3^2 )/(10))+.....=Σ_(n=1) ^∞ ((n(n+1)^2 )/(10^n ))

Q1063791.2210+2.3210+.....=n=1n(n+1)210n

Answered by abdomsup last updated on 05/Aug/20

S=Σ_(n=1) ^∞  ((n(n+1)^2 )/(10^n ))  =Σ_(n=1) ^∞  ((n(n^2 +2n+1))/(10^n ))  =Σ_(n=0) ^∞  (n^3 /(10^n )) +2Σ_(n=0) ^∞  (n^2 /(10^n )) +Σ_(n=0) ^∞  (1/(10^n ))  we have for ∣x∣<1   Σ_(n=0) ^∞  x^n  =(1/(1−x)) ⇒Σ_(n=0) ^∞  (1/(10^n ))  =(1/(1−(1/(10)))) =((10)/9)  also Σ_(n=1) ^∞  nx^(n−1)  =(1/((1−x)^2 )) ⇒  Σ_(n=1) ^∞ nx^n  =(x/((1−x)^2 )) ⇒  Σ_(n=1) ^∞ n^2 x^(n−1 ) =(((x−1)^2 −2(x−1)x)/((x−1)^4 ))  =((x−1−2x)/((x−1)^3 )) =((−x−1)/((x−1)^3 )) =((1+x)/((1−x)^3 )) ⇒  Σ_(n=1) ^∞  n^2 x^n  =((x+x^2 )/((1−x)^3 )) ⇒  Σ_(n=1) ^∞  (n^2 /(10^n )) =(((1/(10))+((1/(10)))^2 )/((1−(1/(10)))^3 )) =...  Σ_(n=1) ^∞ n^3 x^(n−1)  =(((2x+1)(1−x)^3 +3(1−x)^2 (x^2 +x))/((1−x)^6 ))  =(((2x+1)(1−x)+3x^2  +3x)/((1−x)^4 ))  =((2x+1−2x^2 −x+3x^2  +3x)/((1−x)^4 ))  =((x^2 +4x+1)/((1−x)^4 )) ⇒  Σ_(n=1) ^∞  n^3  x^n  =((x^3  +4x^2  +x)/((1−x)^4 )) ⇒  Σ_(n=1) ^(∞ )  (n^3 /(10^n )) =(((1/(10^3 ))+(4/(10^2 ))+(1/(10)))/((1−(1/(10)))^4 ))=...

S=n=1n(n+1)210n=n=1n(n2+2n+1)10n=n=0n310n+2n=0n210n+n=0110nwehaveforx∣<1n=0xn=11xn=0110n=11110=109alson=1nxn1=1(1x)2n=1nxn=x(1x)2n=1n2xn1=(x1)22(x1)x(x1)4=x12x(x1)3=x1(x1)3=1+x(1x)3n=1n2xn=x+x2(1x)3n=1n210n=110+(110)2(1110)3=...n=1n3xn1=(2x+1)(1x)3+3(1x)2(x2+x)(1x)6=(2x+1)(1x)+3x2+3x(1x)4=2x+12x2x+3x2+3x(1x)4=x2+4x+1(1x)4n=1n3xn=x3+4x2+x(1x)4n=1n310n=1103+4102+110(1110)4=...

Answered by Dwaipayan Shikari last updated on 05/Aug/20

Σ^∞ ((n(n+1)^2 )/(10^n ))  Σ^∞ (n^3 /(10^n ))+Σ^∞ ((2n^2 )/(10^n ))+Σ^∞ (n/(10^n ))  Σ^∞ (n/(10^n ))=(1/(10))+(2/(10^2 ))+...=S  (S/(10))=(1/(10^2 ))+(2/(10^3 ))+....  ((9S)/(10))=(1/(10))+(1/(10^2 ))+(1/(10^3 ))+...  ((9S)/(10))=((1/(10))/(1−(1/(10))))=(1/9)  S=((10)/(81))  2Σ^∞ (n^2 /(10^n ))=(1/(10))+(4/(10^2 ))+(9/(10^2 ))+....=S′  ((S′)/(10))=(1/(10^2 ))+(4/(10^3 ))+(9/(10^4 ))+...  ((9S′)/(10))=(1/(10))+(3/(10^2 ))+(5/(10^3 ))+...  ((9S^′ )/(100))=         (1/(10^2 ))+(3/(10^3 ))+...  ......subtracting  ((9S′)/(10))(1−(1/(10)))=(1/(10))+2((1/(10^2 ))+.....)  ((81S′)/(100))=(2/9)−(1/(10))  S′=((10)/9).((11)/(81))=((110)/(729))  Σ^∞ ((n^3 /(10^n )))=(1/(10))+(8/(10^2 ))+((27)/(10^3 ))+...=S_n   S_n +2S′+S=Σ^∞ (n^3 /(10^n ))+((220)/(729))+((10)/(81))=((1400)/(2187))

n(n+1)210nn310n+2n210n+n10nn10n=110+2102+...=SS10=1102+2103+....9S10=110+1102+1103+...9S10=1101110=19S=10812n210n=110+4102+9102+....=SS10=1102+4103+9104+...9S10=110+3102+5103+...9S100=1102+3103+.........subtracting9S10(1110)=110+2(1102+.....)81S100=29110S=109.1181=110729(n310n)=110+8102+27103+...=SnSn+2S+S=n310n+220729+1081=14002187

Answered by JDamian last updated on 06/Aug/20

S = Σ_(k=1) ^(∞) ((k(k+1)^2 )/(10^k ))  f ≡ f(x) = 1+x^2 +x^3 + ∙∙∙ = (1/(1−x))    ∀∣x∣<1  D ≡ (d/dx)  Df = 1+2x+3x^2 + ∙∙∙ = (1/((1−x)^2 ))   ∀∣x∣<1  x^2 Df = 1∙x^2 +2x^3 + ∙∙∙ = (x^2 /((1−x)^2 ))   ∀∣x∣<1  D(x^2 Df) = 1∙2x+2∙3x^2 +3∙4x^3 + ∙∙∙ =                        = 2(x/((1−x)^3 ))      ∀∣x∣<1  xD(x^2 Df) = 1∙2x^2 +2∙3x^3 +3∙4x^4 + ∙∙∙ =                           = 2(x^2 /((1−x)^3 ))      ∀∣x∣<1  g≡D(xD(x^2 Df)) = 1∙2^2 x+2∙3^2 x^2 +                                           +3∙4^2 x^3 +4∙5^2 x^4 + ∙∙∙ =                                          = 2(((2+x)x)/((1−x)^4 ))        ∀∣x∣<1    g((1/(10)))=2(((2+(1/(10)))(1/(10)))/(((9/(10)))^4 ))=2(((21)/(100))/(((9/(10)))^4 ))=((4200)/9^4 )=((4200)/(6561))

S=Σk=1k(k+1)210kff(x)=1+x2+x3+=11xx∣<1DddxDf=1+2x+3x2+=1(1x)2x∣<1x2Df=1x2+2x3+=x2(1x)2x∣<1D(x2Df)=12x+23x2+34x3+==2x(1x)3x∣<1xD(x2Df)=12x2+23x3+34x4+==2x2(1x)3x∣<1gD(xD(x2Df))=122x+232x2++342x3+452x4+==2(2+x)x(1x)4x∣<1g(110)=2(2+110)110(910)4=221100(910)4=420094=42006561

Terms of Service

Privacy Policy

Contact: info@tinkutara.com